Large strain in lead-free piezoelectric (1−x−y)Bi0.5Na0.5TiO3–xBi0.5K0.5TiO3–yBi0.5Li0.5TiO3 system near MPB prepared via the combustion technique. (July 2015) - Sumang, Rattiphorn; Cann, David P.; Kumar, Nitish; Bongkarn, Theerachai
Abstract: Lead-free ferroelectric ceramics in the (1− x − y )Bi0.5 Na0.5 TiO3 – x Bi0.5 K0.5 TiO3 – y Bi0.5 Li0.5 TiO3 (1− x − y BNT– x BKT– y BLT) ternary system with 0.18≤ x ≤0.26 and 0≤ y ≤0.12 were prepared by the combustion technique. The effects of x and y contents on the crystal structures and electrical properties were examined. The results indicated that a coexistence of rhombohedral ( R ) and tetragonal ( T ) phases occurs in the system, which tends to evolve into tetragonal symmetry when the x and y contents are increased. The diffuseness exponent ( γ ) of the ceramics was between 1.6 and 1.9, indicating that the (1− x − y )BNT– x BKT– y BLT solid solutions exhibited diffuse phase transition behavior. The change in P – E loops indicated that the long-range ferroelectric order of the sample was affected and transitioned to the polar nano-region with increase of x and y contents. The polarization hysteresis loop transitioned from well saturated loops a typical of a normal ferroelectric to a pinched loop and finally to a relaxor state with the increase of x and y contents. The coexistence of polar and non-polar phases at the MPB (0.77BNT–0.20BKT–0.03BLT) likely caused the pinching behavior with large strains of approximately ~0.36% (measured at 5 kV/mm) and S max / E max values of ~727 pm/V which are suitable for actuator applications.